Determinants of direct democracy - Nadia Fiorino; Roberto Ricciuti (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper investigates on the demographic, economic, political and cultural determinants of direct democracy in 87 countries using an index of direct democracy. The test is interesting since there are important variations across these countries in the referendum and initiative use. We apply a number of estimation techniques. We find that per capita income, education and a larger share of Catholic population are positive determinants, whereas ethnic fractionalization is depending on the estimation technique. Political rights and stability also work as prerequisites to direct democracy. Direct democracy seems independent from the institutional structure.
Keywords: H80; 330; Demokratie; Referendum; Policy-Ansatz; Vergleich; Schätzung; Welt